The effects of health education program on knowledge and attitudes of people suffering from hypertention - Nahid Jalilian; Sedigheh Sadat Tavafian; Teamur Aghamolaei; Samira Ahmadi (Iranian Association of Health Education and Health Promotion, 2014)
Introduction: There are substantial evidences that unhealthy behaviors regarding hypertension disease could result in consequences of the disease and increased mortality rate. This study aimed to assess the efficacy of health education program to improve knowledge and attitudes of patients regarding due self cares. Material and method: This is a before and after interventional trial that was undertaken among hypertension patients who referred to health centers in south Tehran, Iran. Totally, 60 eligible patients were randomly selected for them a designed educational program was accomplished. Then knowledge, attitudes of participants regarding hypertension was assessed before and after intervention through a self administered questionnaire. Results: The results of this study showed mean scores of knowledge and attitudes were significantly improved after intervention (67.6±18.8 vs 92.0 ± 5.4 for knowledge and 55.3 ± 15.4 vs 87.8 ± 8.6 for attitude) (all P value< 0.0001). Conclusion: The findings of this study suggest that the designed educational program is an effective intervention and could play an important role in improving knowledge and attitudes of hypertension disease.